2021
DOI: 10.1111/ajco.13553
|View full text |Cite
|
Sign up to set email alerts
|

Patient demographics and management landscape of metastatic colorectal cancer in the third‐line setting: Real‐world data in an australian population

Abstract: Background: Colorectal cancer is the third most common cancer and second leading cause of cancer mortality in Australia, thus carrying a significant disease burden.Aims: This analysis aims to explore real-world treatment landscape of metastatic colorectal cancer in the third-line setting. Methods:We retrospectively analysed treatment of recurrent and advanced colorectal cancer (TRACC) registry database from 2009 onwards. Patients treated with e56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…The TRACC registry is a multi‐site registry maintained by BioGrid Australia with 14 sites across Australia and further sites in Hong Kong, commenced in 2009. Nine out of 14 sites are based in Victoria 21 . It prospectively records patients with recurrent and synchronous or metachronous metastatic colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRACC registry is a multi‐site registry maintained by BioGrid Australia with 14 sites across Australia and further sites in Hong Kong, commenced in 2009. Nine out of 14 sites are based in Victoria 21 . It prospectively records patients with recurrent and synchronous or metachronous metastatic colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Nine out of 14 sites are based in Victoria. 21 It prospectively records patients with recurrent and synchronous or metachronous metastatic colorectal cancer. It has comprehensive detail on chemotherapy and targeted therapy treatments as well as toxicity effects, treatment adverse events and disease progression.…”
Section: Treatment Of Recurrent and Advanced Colorectal Cancer (Tracc...mentioning
confidence: 99%
“…Clinicians will determine individualized third-line therapy based on molecular characteristics, previous used regimens, residual toxicity, accessible drugs and so on. In a real-world study of mCRC in Australia, the majority of patients chose chemotherapy as their third-line therapy and more than four-fifths of them were given as chemotherapy rechallenge [ 21 ]. Similarly, more mCRC patients in our study chose third-line chemotherapy (78.1%) and the re-challenge rate was 65%.…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world study from Australia, the choice of third-line treatment varies according to KRAS status and novel drugs availability in clinical trials. 23 In this Australian cohort, the majority of patients chose chemotherapy as their third-line therapy, and 83% of them were given as chemotherapy rechallenge. 23 Another Japanese retrospective study also showed that chemotherapy rechallenge was a valuable option and was more effective than regorafenib in the third-line setting for mCRC patients.…”
Section: Introductionmentioning
confidence: 98%
“… 23 In this Australian cohort, the majority of patients chose chemotherapy as their third-line therapy, and 83% of them were given as chemotherapy rechallenge. 23 Another Japanese retrospective study also showed that chemotherapy rechallenge was a valuable option and was more effective than regorafenib in the third-line setting for mCRC patients. 24 For the real-world treatment patterns of Chinese patients with mCRC, the most common sequence from first-line to second-line was from FOLFOX or other oxaliplatin-based regimens to FOLFIRI or other irinotecan-based schemes.…”
Section: Introductionmentioning
confidence: 98%